Engineering Intangibles: Technical Employment in the US Service Economy. Issue 3 (2nd September 2022) - Alic, John A.
Abstract : Engineering occupations coevolved with industries producing material outputs: mining, construction, manufacturing. Yet wealthy economies have long been moving toward intangible services, the products of industries including finance, wholesale and retail trade, entertainment, travel and transportation, health care, and the public sector (including, e.g. much of education). For the United States the shift is evident in statistical data going back well over a century and services now account for nearly 90 percent of all employment. The job share is lower for engineers, but even so the majority work for service-producing entities. Entanglement and interdependence of services and goods hinders understanding of the dynamics, as does rapid growth in jobs classed in official employment statistics as computer-related even though much of the work resembles engineering. Because of this, field studies that explore actual job content will be needed to develop clearer pictures of the everyday tasks employers assign technical workers in postindustrial economies.